Effect of Impact on Pre-Squibbed Fireworks - Yasutaka Dote; Paul Worsey (International Society of Explosives Engineers, 2009)
The choreography of large fireworks displays dictates electric initiation for precise timing. It has been common practice to pre-squib products before transportation for reducing set up time. A number of fatal accidents transferring pre-squibbed product during transportation suggests that there is a problem with impact sensitivity. The aim of this paper is to quantify the impact sensitivity of the various configurations of initiating materials used in display fireworks.